Implementasi E-Modul Berbantuan Google Sites dengan Model PBL dalam Pembelajaran IPS untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik - Efendi, Bintang Muhammad Sahara; Insani, Nailul (Jurnal Riset dan Inovasi Pembelajaran, 2024)
Low interest in learning in Social Studies subjects is a challenge faced by educators in schools. This low interest in learning is caused, in part, by teachers' lack of creativity in adapting to students' needs and desires during the learning process in class. To overcome this, this study is needed which aims to describe the results of the implementation of E-Modules assisted by Google Sites with the Problem Based Learning model in social studies learning to increase the interest and learning outcomes of class VIII students. This research used a quasi-experiment design with one group pre-test and post-test. Data was collected from observations, interviews, questionnaires, and documentation, which in this case was specifically from students in class VIII-J. The results of this research indicate an increase in students' interest in learning and learning outcomes after the treatment was carried out in the classroom. The use of E-Modules and PBL models has a positive influence on students' learning interest and learning outcomes.